Great Game or Great Confusion: The Geopolitical Understanding of EU-Russia Energy Relations. Issue 4 (1st October 2016) - Casier, Tom
ABSTRACT: This article explains why a considerable part of the International Relations literature frames highly complex energy relations between the EU and Russia in terms of simple, exclusive geopolitical intentions. Drawing on Construal Level Theory, it addresses the gap between immediate interaction between various private and public actors with their own agendas and individual intentionalities and assumed collective geopolitical intentionalities. Because of the degree of abstraction, collective motivations are attributed to actors like Russia and the EU. This attribution risks to be subject to bias. It is argued that higher psychological distance increases the likelihood of more radical and ideologised framing. These abstract schemes do not follow from the endogenous energy dynamics but are function of a broader logic of competition which has characterised EU-Russia relations.